Analisa Kadar Timbal Dalam Darah Dengan Kadar Hemaglobin Dan Hematokrit Pada Supir di Kota Palembang - Lubis, Agnes Felicia; Ch, Lidwina Septie (Jurnal Laboratorium Khatulistiwa, 2024)
Palembang City is a major urban center located on the island of Sumatra that has experienced substantial growth and development. The rapid increase in population and industrial activity has led to widespread contamination of water, food, and beverages with heavy metals. This is worsened by other variables, including smoking habits and work-related issues. At now, there is a limited number of papers that examine blood as a biomarker for lead contamination, particularly in Palembang City. These articles mostly focus on study participants that are very likely to be exposed, such as drivers. The objective of this study was to evaluate the blood lead levels in a cohort of drivers in Palembang City as an indicator of lead pollution. The participants in this study were drivers, with an average age of 58 years, who had accumulated more than 20 years of work experience (average 28 years). Utilizing the APHA technique, quantifying blood lead concentrations, and employing the impedance method and Spearman test to establish a correlation between the results, evaluating hemoglobin and hematocrit levels. The research findings indicate a correlation between blood lead levels and hemoglobin values (significance: 0.037) as well as hematocrit (significance: 0.039). The mean blood lead concentrations in drivers remain below the threshold of 14.9804 µg/L. The investigation conducted indicates a clear association between the levels of lead in the blood and the values of hemoglobin and hematocrit in the blood of drivers in Palembang City. A strong association was seen between blood lead levels and hemoglobin and hematocrit values